(untitled) (Proceedings of Southern Federal University. Philology, 2014)
This article discusses the basics of the theory of speech genres. The paper describes the features of the speech genre of “Dialogue between a doctor and a sick” in terms of composition, style and concept of the addressee. The main attention is paid to the analysis of primary facultative genres that may arise in the communication “doctor-patient”, as well as extralinguistic causes of them. It is postulated that the concept of dialogue as a sequential exchange of remarks between the two partners, participants of the dialogue does not reflect the complexity and nature of the feature of this type of communication. The paper substantiates the importance of mastering the genre of speech data for the success of the communication in the professional dialogic communication of foreign medical students. Works of writers-doctors (“Notes doctor” by V.V. Veresaeva, “A Young Doctor’s Notebook” Bulgakov, “Thoughts and Heart” Amosov) are considered from the point of view of their lingua didacti potential that can be used for formation of communicative abilities. Key words: speech genre, communicative competence, sender, addressee, frame, optional speech genres.